Information support model and its impact on utility, satisfaction and loyalty of users - Šadić, Sead; Puška, Adis; Beganović, Admir (The European Journal of Applied Economics, 2016)
In today’s modern age, information systems are of vital importance for successful performance of any organization. The most important role of any information system is its information support. This paper develops an information support model and presents the results of the survey examining the effects of such model. The survey was performed among the employees of Brčko Distric Government and comprised three phases. The first phase assesses the influence of the quality of information support and information on information support when making decisions. The second phase examines the impact of information support when making decisions on the perceived availability and user satisfaction with information support. The third phase examines the effects of perceived usefulness as well as information support satisfaction on user loyalty. The model is presented using six hypotheses, which were tested by means of a multivariate regression analysis. The demonstrated model shows that the quality of information support and information is of vital importance in the decision-making process. The perceived usefulness and customer satisfaction are of vital importance for continuous usage of information support. The model is universal, and if slightly modified, it can be used in any sphere of life where satisfaction is measured for clients and users of some service.
Keywords: information system; information support model; loyalty; satisfaction; information support